Seed Yield Components and Seed Quality of Oilseed Rape Are Impacted by Sulfur Fertilization and Its Interactions With Nitrogen Fertilization - Poisson, Emilie; Trouverie, Jacques; Brunel-Muguet, S.; Akmouche, Yacine; Pontet, Célia; Pinochet, Xavier; Avice, Jean-Christophe (Frontiers in Plant Science, 2019)
Although the impact of sulfur (S) availability on the seed yield and nutritional quality of seeds has been demonstrated, its impact coupled with nitrogen (N) availability remains poorly studied in oilseed rape. A deeper knowledge of S and N interactions on seed yield components and seed quality could improve S and N fertilization management in a sustainable manner. To address this question, our goals were to determine the effects of 9 different S fertilization management strategies (i) in interaction with different levels of N fertilization and (ii) according to the timing of application (by delaying and fractionating the S inputs) on agronomic performances and seed nutritional quality in oilseed rape. Our results highlighted synergetic effects on S and N use efficiencies at optimum rates of S and N inputs and antagonistic effects at excessive rates of one of the two elements. The data indicated that adjustment of S and N fertilization may lead to high seed yield and seed protein quality in a sustainable manner, especially in the context of reductions in N inputs. Because delaying S inputs improved the seed protein quality by significantly increasing the relative abundance of napin, our observations suggest that fractionated or delayed S fertilizer inputs could provide additional insights into the development of N and S management strategies to maintain or improve seed yield and quality. In addition, we demonstrated that the S% and the napin:30 kDa-cruciferin ratio, which could be used as a relevant index for the determination of protein quality in seeds, is highly dependent on S/N fertilization in relation to S supply.